ROLE OF AHARA AND VIHARA IN MANAGEMENT OF TAMAKA SHWASA - Chouhan, Dinesh C; Dadhich, . Om Prakash; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2019)
Ayurveda is the science of life dealing with physical, psychological as well as spiritual well-being of an individual. The Srotas in which Pranavayu flows is known as Pranvaha Srotas. Any derangement in the normal physiological values of the Pranvaha Srotas may lead to several GI, cardiac and respiratory disorders. Tamaka Shwasa shows close resemblance with bronchial asthma on the basis of clinical manifestations. According to Ayurveda, Tamaka Shwasa is a Pitta sthana Samudhabhava and Kaphavataja Vyadhi. Whenever there is obstruction of Prana Vayu by Kapha Dosha, the vitiated Vayu gets Pratiloma to produce Tamaka Shwasa. A look at the Nidana of Shwasa show that Raja, Dhooma, SheetambuSevena etc. are the causative factors for Shwasa. The Nidana focus on aggravating Vata and Kapha like Guru Bhojan, Pishtanna etc. Sushruta mentions the intake of Ruksha and AbhishyandiBhojana as the cause of Shwasa. Thus, the aim of lifestyle in a patient of Shwasa should be to leave these foods and incorporate such food & drinks which are Ushna, Kapha-Vatahara and help in VataAnulomana i.e. putting Vata in its normal Marga. This will, in turn, help in clearing the PranavahaSrotas and relieving the symptoms of Tamaka Shwasa. This will also prevent the further relapse of the Tamaka Shwasa symptoms.The present article is a review on the lifestyle modification through Ahara and Vihara in Tamaka Shwasa.